Effect of Counseling on Health Related Quality of Life on Haemodialysis Patients - Ramakrishanan Sivakumar; Merin M. Stephen; Sreedas Sreedas; Rajesh Joseph (Universitas Padjadjaran, 2012)
End stage renal disease affects two million patients worldwide. Health related quality of life (HRQoL) has recently become a major indicator of health and well-being of patients with kidney disease. The present goal for the treatment of patients with ESRD is not simply to prolong life, but also to provide a better HRQoL. This goal can be achieved through patient counseling. A simple prospective study was used to examine the effect of patient counseling on HRQoL of hemodialysis patients. In the study, a Short Form-36 (SF-36) questionnaire and clinical parameters were used for 52 hemodialysis patients to assess the HRQoL before and after patient counseling. All the Patients were kept under observation for a period of three months to study the effect of patient counseling. After three months period of counseling a significant (p<0.05) improvement was observed for hemodialysis patients. Also HRQoL score was higher for hemodialysis patients after counseling. This study concluded that knowledge of the disease and its management through patient counseling could improve the HRQoL of hemodialysis patients.Key words: Chronic renal failure, patient education, quality life improvement Pengaruh Konseling terhadap Health Related Quality of Life pada Pasien HemodialisisAbstrakPenyakit ginjal pada stadium akhir (End Stage Renal Disease/ESDR) memengaruhi dua juta pasien di seluruh dunia. Saat ini health related quality of life (HRQoL) telah menjadi indikator utama kesehatandan kesejahteraaan pasien dengan penyakit ginjal. Tujuan pengobatan pasien ESDR tidak hanya untukmemperpanjang usia harapan hidup namun juga untuk menyediakan HRQoL yang lebih baik. Tujuan ini dapat dicapai melalui konseling pasien. Sebuah studi prospektif dilakukan untuk menguji pengaruh dari konseling pasien pada HRQOL dari pasien hemodialisis. Dalam studi ini, sebuah kuesioner Short Form-36 (SF-36) dan parameter klinik digunakan pada 52 pasien hemodialisis untuk menilai HRQOL sebelum dan sesudah konseling. Seluruh pasien diamati dalam jangka waktu tiga bulan untuk mempelajari pengaruh konseling tersebut. Setelah tiga bulan proses konseling diperoleh peningkatan nilai HRQoL yang signifikan (p <0,05) pada pasien hemodialisis. Penelitian ini menyimpulkan bahwa pengetahuan tentang penyakit dan manajemen melalui konseling pasien bisa meningkatkan HRQoL pada pasien hemodialisis.Kata kunci: Gagal ginjal kronis, edukasi pasien, peningkatan kualitas hidup